CLAVATA2 forms a distinct CLE-binding receptor complex regulating Arabidopsis stem cell specification - Guo, Yongfeng (2010)
CLAVATA1 (CLV1), CLV2, CLV3, CORYNE (CRN), BAM1 and BAM2 are key regulators that function at the shoot apical meristem (SAM) of plants to promote differentiation by limiting the size of the organizing center that maintains stem cell identity in neighboring cells. Previous results have indicated that the extracellular domain of the receptor-kinase CLV1 binds to the CLV3-derived CLE ligand. The biochemical role of receptor-like protein CLV2 has remained largely unknown. While genetic analysis suggested that CLV2, together with the membrane kinase CRN, act in parallel with CLV1, recent studies using transient expression indicated that CLV2 and CRN from a complex with CLV1. Here we report evidence for distinct CLV2/CRN heteromultimeric and CLV1/BAM multimeric complexes in transient expression and in Arabidopsis. Weaker interactions between the two complexes were detectable in transient expression. We also find that CLV2 alone generates a membrane-localized CLE binding activity independent of CLV1. CLV2, CLV1 and the CLV1 homologs BAM1 and BAM2 all bind to the CLV3-derived CLE peptide with similar kinetics, but BAM receptors show a broader range of interactions with different CLE peptides. Finally, we show that BAM and CLV1 over-expression can compensate for the loss of CLV2 function in vivo. These results suggest two parallel ligand-binding receptor complexes controlling stem cell specification in Arabidopsis.